Pengaruh gaya kepemimpinan dan stres kerja terhadap kinerja karyawan RSU. Queen Latifa Yogyakarta - Suhartini, Tien; Ramadhan, Rifqi Andika (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2021)
The purpose of this study was to empirically examine the effect of leadership style and work stress on employee performance at Queen Latifa General Hospital Yogyakarta. This type of research is quantitative research with causal associative design. The population of this study were permanent and contract employees at the front office of Queen Latifa General Hospital Yogyakarta. The number of samples in this study were 35 respondents. The data analysis method used is Multiple Regression Analysis, T Test (Partial), F Test (Simultaneous Significance Test), Coefficient of Determination Test (R2). The results of this study indicate that leadership style has a positive and significant effect on employee performance, while job stress has no effect on employee performance. The results of the F test obtained a calculated F value of 4.609 with a sig value of 0.017, which means that the independent variables have a simultaneous effect, although not significant. R Square value of 0.224 which means that employee performance is influenced by leadership style and work stress by 22.4%, while the remaining 77.6% is explained by other variables not examined in this study.